Effects of the Angled Blades of Extremely Small Wind Turbines on Energy Harvesting Performance - Junseon Park; Seungjin Lee; Joong Yull Park (Mathematics, 2020)
Low-intensity winds can be useful power sources in the context of energy harvesting. This study aims to enhance the power generation capacity of a super micro wind turbine (SMWT) in low-intensity winds by modifying the blade geometry, which cannot be realized in conventional wind turbines owing to the stress concentration. By controlling the curved angle (θ) in the middle of the blade, the rotor performance can be improved, and the rotor diameter can be reduced to increase installation density. Experimental results indicated that the optimal θ value was 105°, at which the AC voltage was improved by 7.4% compared to that in the case of the basic model with θ = 0°. The maximum electric power output was 9.333 μW and the load resistance was 47.62 kΩ. Moreover, a computational fluid dynamics analysis was performed to clarify the pressure field and streamlines on and around the blade to demonstrate the aerodynamic performance of the SMWT. The proposed blade geometry is one of many possible designs that can enhance extremely small wind turbines for energy harvesting.